To calculate the value of (-m)^-3 * n, we substitute the given values of m and n.
Given: m = 2 and n = -24
(-m)^-3 = (-2)^-3
This means we raise -2 to the power of -3.
(-2)^-3 = -1/(2^3) = -1/8
Now, we can substitute the values of (-m)^-3 and n into the expression:
(-m)^-3 * n = (-1/8) * (-24) = 3
Therefore, (-m)^-3 * n equals 3 when m equals 2 and n equals -24.
What is left parenthesis negative m right parenthesis superscript negative 3 baseline n if m equals 2 and n equals negative 24 question mark
1 answer